Sustainability Practices and Financial Performance of Non-Financial Quoted Firms in Nigeria - Akerele, Ezekiel Olaoluwa; Okewale, Joel Adeniyi; Adeyemo, Paul Adeniyi (Acta Universitatis Danubius. Œconomica, 2024)
The study examined the impact of sustainability practices on the financial performance of non-financial quoted firms in Nigeria. The research design adopted for the study is ex-post facto covering a ten-year period from 2011 to 2020 and the focused population is all the 64 companies across five sectors of the Nigerian Stock Exchange namely oil & gas, consumer goods, industrial goods, healthcare, and ICT sectors. The study adopted stratified sampling techniques to select 56 firms while secondary data sourced from annual reports, sustainability reports, codes of business conduct and ethics, and other stand-alone reports of the selected firm were used for the study, a multiple regression analysis technique was utilized for the models which were tested at 5% level of significantwith the aid of Stata 14.1 software of the statistical package for the analysis of the data. The study as revealed by the Fixed Effects Model (FEM) analysis showed no statistically significant association between sustainability practicesand ROA which has Environment index coefficient as 0.011 and p-value of 0.973, Social index coefficient as 7.077 and p-value of 0.358, and Ethical index coefficient as 11.867 and p-value of 0.874. Similarly, the Pooled Ordinary Least Squares (POLS) regression analysis found no significant relationships between sustainability practices and ROEwhit the coefficient for the three sustainability metricsare 0.218, 70.615 and 36.824, while their p-value are 0.863, 0.247 and 0.397 respectively. Again, the POLS regression analysis revealed no significant associations between sustainability practices and NPM as the coefficient for the three proxy of sustainability practices stands as 0.351, 7.877 and -19.656 while their p-value are 0.893, 0.95, and 0.439. The overall results based on the models and data used in the study suggest that sustainability practices do not have a significant influence on the financial performance metrics (ROA, ROE, and NPM) of non-financial firms in Nigeria. The study concluded that there is a weak correlation between sustainability practices and financial performance of non-financial quoted firms in Nigeria and their statistical relationship is not significant. It is recommended that companies in Nigeria adopt sustainable practices as a business strategy rather than as a compliance requirement in order to match up with global trends.